Comparação dos valores medidos e preditos de pressões respiratórias máximas em escolares saudáveis - criação de uma nova equação de referência preditiva de força muscular respiratória - Lidia Miranda Barreto (2012)
The Respiratory Muscle Strength, defined as the maximum pressure measured at the mouth and reflected by measurements of inspiratory and expiratory muscle strength, form an important arsenal capable of diagnosing and predicting neuromuscular and pulmonary disorders. It is influenced by several factors, and nowadays there are several reference predictive equations described considering different populations and methodologies. However, there is no consensus of ideal values, and there are few reports in the literature of predictive equations of maximal respiratory pressures in children and adolescents in Brazil. OBJECTIVES In this context, this study aimed to measure and compare values of respiratory muscle strength in healthy children and adolescents of school system in Belo Horizonte with the values predicted by the proposed equations described by Wilson et al., Domènech et al. and Schmidt et al. more commonly used in databases together with analysis of lung function and anthropometric data, thus reinforcing the need to propose the creation of a reference equation predictive of maximal respiratory pressures in this population. METHODS This was a cross-sectional and convenience sample consisted of 90 healthy children and adolescents aged 6-12, with 44 females (39.6%) and 46 males (41.4%). Individuals were classified according to BMI proportional to age, being all normal and healthy, with no current or past pathologic conditions. The spirometer VITATRACE VT 130 was used for spirometry measurements and FVC, FEV1, to ensure the normal lung function. The anthropometric measurements were taken were weight, height, arm circumference and triceps skinfold thickness. The manometer GERAR was used for the measurement of maximal respiratory pressures. One questionnaire were used (ISAAC) for refinement of data analysis, characterization of subjects and homogenization of the sample. STATISTICAL ANALYSIS The distribution of the samples was verified by the Kolmogorov-Smirnov test and / or Shapiro-Wilk test, unpaired t-test to compare the sexes, analysis of variance (ANOVA) and post hoc Student-Newman-Keuls (SNK) for comparisons measured and predicted values, Pearson correlation test to measure the association between variables and multiple linear regression to model the proposed reference equations and make predictions. The significance level was 5%. RESULTS / CONCLUSION The comparison of measured and predicted values for maximal respiratory pressures are significantly different, and the reference equations were not able to predict the values of MIP and MEP in the population studied, and thus, this study proposed a new predictive equation respiratory muscle strength considering this population.